L’humour comme combinaison des contradictions. Une approche esthétique - Uzel, Jean-Philippe (RACAR : Revue d'art canadienne / Canadian Art Review, 2012)
This essay aims to establish that humour is not simply a style or an artistic genre among others, but is, rather, a core philosophical concept that permeates reflections on art from the end of the eighteenth century to the present day. Romantic philosophers were the first to contend that humour marked a new reign of artistic subjectivity. Indeed, the philosophical aesthetics of Jean Paul (Johann Paul Friedrich Richter) and Hegel award humour a paramount role in the aesthetic revolution of the time. Whether they revel in it (Jean Paul) or deplore it (Hegel), they are the first to bring to light the observation that humour allows contradictory realities to coexist without friction and within a single artistic proposition. It is precisely this idea that reappears, roughly a century later, in the techniques of Dadaist assemblage, in which Marcel Duchamp saw a manifestation of the “co-intelligence of the opposites.” Recent writings by Jacques Rancière support the view that Schiller, Schelling, Hegel, among others, were the first philosophers to propose a new form of identification and of perception of art. This “aesthetic regime of art” was no longer based on the laws of mimetic representation, but rather on “the mixing of heterogeneous elements.” Building on this theoretical framework, this essay demonstrates that Rancière nevertheless overlooks the key function that humour plays in romantic aesthetics and for the historical avant-gardes.